Answer: 9
Step-by-step explanation: its very simple , first take the -2 out of the parenthesis and put is as 10-2+1 which is positive 9 because 10-2=8 and plus 1 is 9.
There is 1 brother as they would all have the same brother.
P = 2(L) +2(W)
P = 2(4x+3) + 2(2x)
answer
B. 2(4x+3) + 2(2x)
The linear equation is y = -x - 6
Step-by-step explanation:
To form a linear equation from two points lie on the line which the equation represented it
- Find the slope of the line by using the formula
![m=\frac{y_{2}-y_{1}}{x_{2}-x_{1}}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7By_%7B2%7D-y_%7B1%7D%7D%7Bx_%7B2%7D-x_%7B1%7D%7D)
- Then use the slope-intercept form of the equation y = m x + b
- To find the value of b substitute x and y of the equation by the coordinates of one of the two given points
∵ Points (-2 , -4) and (-3 , -3) lie on the line
∴
= -2 and
= -3
∴
= -4 and
= -3
- Substitute these values in the formula of the slope
∵ ![m=\frac{-3-(-4)}{-3-(-2)}=\frac{-3+4}{-3+2}=\frac{1}{-1}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7B-3-%28-4%29%7D%7B-3-%28-2%29%7D%3D%5Cfrac%7B-3%2B4%7D%7B-3%2B2%7D%3D%5Cfrac%7B1%7D%7B-1%7D)
∴ m = -1
∵ The form of the equation is y = m x + b
∵ m = -1
∴ y = (-1) x + b
∴ y = -x + b
To find b substitute x and y in the equation by the coordinates of
point (-2 , -4) OR (-3 , -3)
∵ x = -3 and y = -3
∴ -3 = -(-3) + b
∴ -3 = 3 + b
- Subtract 3 from both sides
∴ -6 = b
∴ The equation is y = -x + (-6)
∴ y = -x - 6
The linear equation is y = -x - 6
Learn more:
You can learn more about linear equation in brainly.com/question/4326955
#LearnwithBrainly